Simbolik Komunikasi Ritual Ukuwala Mahiate Masyarakat Islam Mamala Kabupaten Maluku Tengah - sulaeman sulaeman (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
Ukuwala Mahiate, an integral part of the Muslim community rituals Mamala of Central Mollucas, a fusion of Islamic teachings interaction with indigenous peoples’ local wisdom, accompanied by offerings. This research would like to reveal the meanings of symbolic process ritual communication. This study aims to describe the process of ritual communication society in respect of Ukuwala Mahiate as a ritual. Through subjective interpretive method with ethnographic communication approach, the peoples undertook the construction symbols against Ukuwala Mahiate , has the meaning of the offering, solicitation, and hope. The meaning does not happen by itself, but a communication process in interpreting the process of ritual taking of palm sugar, medicinal oil, appeal and hope, communication action, and treatment of communication actors.